Complete robotic inspection line using PC-based control, supervision and parameterization software - Pires, J. Norberto (2005)
Non-flat ceramic products, like toilets and bidets, are fully inspected at the end of the production process, to search for structural, surface and functional defects. Ceramic pieces are transported to the inspection lines assembled in pallets, carried by electro-mechanical fork-lifters or automatic guided vehicles. Pallets need to be disassembled, while feeding with the inspection lines where human operators execute the inspection tasks. Also, the pieces that pass inspection need to be palletized again for product distribution. Those de-palletizing and palletizing operations are physically very demanding and can be performed with advantages by robots.